Improving Student’s Listening Comprehension in Watching Movie - Astro Julida Harahap (International Journal For Advanced Research, 2025)
There are many problem to convey something to other people if we don’t know their language especially in English Language. There are many methods to improve our language, especially to improve student’s ability. The Objective of the study was to analyse and describe the process of improving students’ listening comprehension for Akademi teknologi Industri Immanuel Medan for the second semester, the students consist of 28. This study was conducted following Planning, acting, observing, and reflecting. the study carried out in two cycles. Every cycle consisted of three and six meetings. The Observation, Interview, Teacher’s journal, and test were the data gathered in this study. The result in this study indicate that there was improvement of the students’ listening. Using Pre- Test and Post – Test. there are a diferent score significant. After the writer used the English Movie to improve student’s ability on listening comprehension and the writer had done Pre-Test and Post-Test. There are a different result significant. using watching English movie in teaching process can improve the student’s abilitiy in Listening.